2000
DOI: 10.1002/(sici)1097-4660(200003)75:3<229::aid-jctb208>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

On the improvement of bacterial growth on complementary substrates by partial segregration in the broth

Abstract: Previous studies have shown that when two species compete for the same substrate, a controlled degree of segregation in a bioreactor favours growth of the desired species. That concept has been extended to the growth of bacteria on a mixture of two substrates for one of which the organism has a natural preference. However, using the example of Escherichia coli cultivated in a medium containing glucose and fumarate, it has been shown that, while the physiological preference for glucose is maintained, incomplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…For D 2 / D 1 = 0.001, the average recombinant cell concentration peaked at 4.5 h, while for larger ratios the fermentation required longer to attain the final (best) state; at D 2 / D 1 = 1.0 the maximum was attained after 5.25 h. Variations in the average substrate concentration, average mass fraction of plasmid‐bearing cells and average plasmid loss probability (Figs 8,9 and 10) with the ratio D 2 / D 1 were also consistent with these observations. The superior performance seen here for D 1 ≠ D 2 , ie a departure from perfect mixing, agrees with similar observations reported earlier7–9 for other recombinant fermentations and strengthens the general validity of exploiting controlled imperfect mixing as a tool to increase the fermentation efficiency of large‐scale bioreactors.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…For D 2 / D 1 = 0.001, the average recombinant cell concentration peaked at 4.5 h, while for larger ratios the fermentation required longer to attain the final (best) state; at D 2 / D 1 = 1.0 the maximum was attained after 5.25 h. Variations in the average substrate concentration, average mass fraction of plasmid‐bearing cells and average plasmid loss probability (Figs 8,9 and 10) with the ratio D 2 / D 1 were also consistent with these observations. The superior performance seen here for D 1 ≠ D 2 , ie a departure from perfect mixing, agrees with similar observations reported earlier7–9 for other recombinant fermentations and strengthens the general validity of exploiting controlled imperfect mixing as a tool to increase the fermentation efficiency of large‐scale bioreactors.…”
Section: Resultssupporting
confidence: 89%
“…Secondly, computations showed that a dilution rate of 10 h −1 was large enough to provide a good approximation of perfect mixing; larger rates produced only marginal changes in the CFSTB performance. However, this value of 10 h −1 may differ from one fermentation system to another and indeed in some cases, nearly perfect mixing may be attained at smaller values of D 1 or D 2 7–9…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation